2019
DOI: 10.1371/journal.pone.0223162
|View full text |Cite
|
Sign up to set email alerts
|

Profiles and trajectories of impaired social cognition in people with Prader-Willi syndrome

Abstract: IntroductionPeople with Prader-Willi syndrome (PWS) have a distinctive behavioral phenotype that includes intellectual disability, compulsivity, inattention, inflexibility and insistence on sameness. Inflexibility and inattention are at odds with the cognitive flexibility and attention to social cues needed to accurately perceive the social world, and implicate problems in social cognition. This study assessed two social cognition domains in people with PWS; emotion recognition and social perception. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 57 publications
4
31
0
1
Order By: Relevance
“…Although our cognitive assessment was only completed by a subset of the larger sample, ndings reveal differential impairment in social cognitive domains, particularly tasks involving processing of faces, implicating cortico-limbic dysfunction (Gur et al, 2017). This pattern of ndings is highly consistent with other recent work in individuals with PWS, involving in-lab assessment (Dykens et al 2019;Debladis et al, 2019). Another recent study offers a translational perspective on psychiatric manifestations of PWS, through the RDoC matrix (Salles et al, 2020): de cits in social processes are highlighted, with eventrelated potential (ERP) evidence that PWS patients have altered processing of faces (Key et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although our cognitive assessment was only completed by a subset of the larger sample, ndings reveal differential impairment in social cognitive domains, particularly tasks involving processing of faces, implicating cortico-limbic dysfunction (Gur et al, 2017). This pattern of ndings is highly consistent with other recent work in individuals with PWS, involving in-lab assessment (Dykens et al 2019;Debladis et al, 2019). Another recent study offers a translational perspective on psychiatric manifestations of PWS, through the RDoC matrix (Salles et al, 2020): de cits in social processes are highlighted, with eventrelated potential (ERP) evidence that PWS patients have altered processing of faces (Key et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…With regard to neurocognition, global cognitive function is typically in the impaired range (average Full Scale IQ of ~ 60, but highly variable, ranging from 40-100 across studies) (Dykens et al, 1992;Whittington & Holland, 2017). De cits in emotion recognition and social perception (i.e., accurately judging the intentions of others) are particularly prominent in individuals with PWS (Dimitropoulos et al, 2019;Dykens et al, 2019). There is also some evidence that cognition may differ as a function of genetic subtype: Torrado et al found that less than 10 percent of subjects with paternal deletion had Full-Scale IQ (FSIQ) 70 or greater, whereas over 60% of subjects without the deletion subtype had FSIQ of 70 or higher (Torrado et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently affected by respiratory malfunction symptoms, sleep disorders, hypogonadism, mild mental deficiency, and disruptions of their endocrine axis. Individuals display behavioral abnormalities including temper tantrums, obsessive compulsion and skin picking [ 4 , 9 , 10 , 11 ]. PWS is a complex disease, and symptoms vary considerably between patients, depending on the size of the chromosomal deletion [ 2 , 12 , 13 ].…”
Section: Prader-willi Syndromementioning
confidence: 99%
“…There is consistent evidence that patients with different neuropsychiatric conditions such as autism [ 9 , 10 ], schizophrenia [ 11 , 12 ], major depressive disorder [ 13 ], bipolar disorder [ 14 , 15 ], Alzheimer’s dementia [ 16 ], or Prader-Willi syndrome [ 17 ] have difficulty in accurately recognising the emotions expressed by others. This deficit can generate a misinterpretation of social situations and, therefore, a significant deficit in social functioning and quality of life [ 18 ].…”
Section: Introductionmentioning
confidence: 99%